Self-layering of (Ti,Al)N by interface-directed spinodal decomposition of (Ti,Al)N/TiN multilayers: First-principles and experimental investigations - Chun Hu; Jie Zhang; Li Chen; Yu X. Xu; Yi Kong; Jian W. Du; Paul H. Mayrhofer (Materials & Design, 2022)
Supersaturated (Ti,Al)N materials with face centered cubic (fcc) structure offer unique combinations of thermal stability and mechanical properties. However, their thermally-induced decomposition processes are crucial for extracting their full potential. Detailed experimental studies by X-ray diffraction and transmission electron microscopy reveal that the formation of the thermodynamically stable wurtzite-type w-AlN starts with 1000 °C at 100 °C lower annealing temperatures (Ta) when applying a multilayer-concept with TiN to form (Ti,Al)N/TiN multilayers. Nevertheless, the hardness of (Ti,Al)N/TiN multilayers peaks with 32.3 ± 1.0 GPa at a 100 °C higher Ta (900 °C) than the (Ti,Al)N coating, and the hardness declining trend with increasing Ta is milder. This is because the (Ti,Al)N decomposes towards a layered structure of Al-rich and Ti-rich regions, when coherently grown with fcc-TiN. Ab initio calculations highlight that Al within the (Ti,Al)N layers preferentially diffuses away from the coherent interface with the TiN layers. Thus, out of one (Ti,Al)N layer more layers form, and even upon the phase-transformation of the Al-rich layers to w-AlN, their layered structure remains. Together, the computational and experimental results suggest that the layered arrangement provides a higher resistance against dislocation glide and is beneficial for the coating integrity.